Effective connectivity of the anterior hippocampus predicts recollection confidence during natural memory retrieval. Issue 1 (December 2018) - Ren, Yudan; Nguyen, Vinh; Sonkusare, Saurabh; Lv, Jinglei; Pang, Tianji; Guo, Lei; Eickhoff, Simon; Breakspear, Michael; Guo, Christine
Abstract Human interactions with the world are influenced by memories of recent events. This effect, often triggered by perceptual cues, occurs naturally and without conscious effort. However, the neuroscience of involuntary memory in a dynamic milieu has received much less attention than the mechanisms of voluntary retrieval with deliberate purpose. Here, we investigate the neural processes driven by naturalistic cues that relate to, and presumably trigger the retrieval of recent experiences. Viewing the continuation of recently viewed clips evokes greater bilateral activation in anterior hippocampus, precuneus and angular gyrus than naïve clips. While these regions manifest reciprocal connectivity, continued viewing specifically modulates the effective connectivity from the anterior hippocampus to the precuneus. The strength of this modulation predicts participants' confidence in later voluntary recall of news details. Our study reveals network mechanisms of dynamic, involuntary memory retrieval and its relevance to metacognition in a rich context resembling everyday life. While memory is often studied using voluntary recollection, the neural correlates of involuntary memory recall and its effect on cognition are unclear. Here, Ren and colleagues show that the effective connectivity from the anterior hippocampus to the precuneus can predict the strength of involuntary retrieval of episodic memory.